2020
DOI: 10.1021/acs.jpcb.0c05092
|View full text |Cite
|
Sign up to set email alerts
|

Charged Dendrimers with Finite-Size Counterions

Abstract: We report on the structure of dendritic polyelectrolytes accompanied by counterions in a good, salt-free, implicit solvent using Langevin dynamics simulations and a Flory-type approach. Our focus is on the modification of charged dendrimer conformations via the strength of electrostatic interactions and the counterion excluded volume. We study the effects caused by charges by varying the reduced Bjerrum length, λB *, between the extremes of weak and strong electrostatic interactions. The counterion excluded vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The treelike structure of the dendrimer consists of the core of two bonded monomers and trifunctional branching groups. The overall number of the monomers, N d , and that of the terminal groups, N t , are given by , N d = 2 + 4 S ( 2 G 1 ) and N t = 2 G + 1 We assign monovalent positive charges to the terminal groups of the dendrimer so that the arrangement of charges corresponds to that of poly(amidoamine) (PAMAM) cationic dendrimers at neutral pH . The anionic surfactant molecules are modeled as chains including a negatively charged monovalent head bead and three hydrophobic tail monomers.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The treelike structure of the dendrimer consists of the core of two bonded monomers and trifunctional branching groups. The overall number of the monomers, N d , and that of the terminal groups, N t , are given by , N d = 2 + 4 S ( 2 G 1 ) and N t = 2 G + 1 We assign monovalent positive charges to the terminal groups of the dendrimer so that the arrangement of charges corresponds to that of poly(amidoamine) (PAMAM) cationic dendrimers at neutral pH . The anionic surfactant molecules are modeled as chains including a negatively charged monovalent head bead and three hydrophobic tail monomers.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Specific ion effects are ubiquitous in chemistry and biology. Previous studies have demonstrated that ion-specific effects, reflected by factors such as sizes and valences of ions, have a great influence on the phase behaviors of different types of PE systems. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have made progresses in understanding the conformational behaviors of a single PE chain as a function of ionic size. Gavrilov et al studied the conformation of a PE chain with small and bulky counterions by the dissipative dynamic simulation method . According to their findings, under conditions of strong electrostatic interactions, bulky asymmetrical counterions prevent ion pairs from forming multiplets, whereas small counterions result in the formation of quadrupoles and small ionic chains .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations